2022
DOI: 10.1590/1678-4162-12592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ZooBioR2 product as feed supplement in laying hens on the morphofunctional state of intestinal mucosa

Abstract: Spirulina platensis is a microalga with biological activity used to produce nutritional supplements rich in proteins, essential fatty acids, vitamins, and minerals. The current study aims to prove the impact of the product ZooBioR2 (obtained from Spirulina platensis) on health, and on the histology of duodenum, jejunum, ileum, and cecum in laying hens. The experiment was performed in duplicate on 5 groups of hens (14 birds/group), one control and four experimental, in which the feed was supplemented with ZooBi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…A. platensis is the most cultivated microorganism worldwide [ 6 ]. Spirulina platensis is a microalga with biological activity that is used to produce nutritional supplements rich in vitamins, proteins, essential fatty acids, and minerals [ 7 ]. Arthrospira is a blue-green photosynthetic filamentous alga that contains phycobiliprotein pigments (PC, phycoerythrin, and allophycocyanin), 15%–25% carbohydrates, 18% essential fatty acids, 55%–70% proteins, vitamins, and minerals.…”
Section: Introductionmentioning
confidence: 99%
“…A. platensis is the most cultivated microorganism worldwide [ 6 ]. Spirulina platensis is a microalga with biological activity that is used to produce nutritional supplements rich in vitamins, proteins, essential fatty acids, and minerals [ 7 ]. Arthrospira is a blue-green photosynthetic filamentous alga that contains phycobiliprotein pigments (PC, phycoerythrin, and allophycocyanin), 15%–25% carbohydrates, 18% essential fatty acids, 55%–70% proteins, vitamins, and minerals.…”
Section: Introductionmentioning
confidence: 99%
“…The mucosa of the duodenum undergoes an important physiological stress in order to neutralize the acidity of the content coming from the stomach. In a previous experiment (Bondar et al, 2022), which assessed the influence of Spirulina platensis extract (ZooBioR2) on the morphology of intestinal segments (duodenum, jejunum, ileum, cecum), it was found that the duodenum reacted most significantly.…”
Section: Introductionmentioning
confidence: 99%